The Effect of Applying the Probing Prompting Learning Model Based on a Scientific Approach to Student Learning Outcomes in Social Arithmetic Mathematics Learning - Amrina Rosada (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to describe the effect of applying the probing prompting learning model based on a scientific approach to student learning outcomes at SMP N 9 Muaro Jambi. Methodology: This type of research is descriptive research with a quantitative approach. The research design used was a random pretest posttest design. The research instruments are tests for the realm of knowledge and observation sheets for the realm of attitudes and skills. Data analysis to find out the average difference in the realm of knowledge used the one-tailed t test. Determination of increased learning outcomes using N-Gain. The description of the effect of applying the model is from the attitude and skills observation sheet. Main Findings: The probing prompting learning model based on a scientific approach influences student learning outcomes. Novelty/Originality of this study: As material for contributing ideas in order to develop the process of learning mathematics at the junior high school level or equivalent, especially in social arithmetic material.